Materials Properties for the Simulation of Electro-Chemo-Mechanical Coupling Behavior of SOFC. (30th May 2017) - Yashiro, Keiji; Kawada, Tatsuya; Watanabe, Satoshi; Muramatsu, Mayu; Sakamoto, Tadashi; Hashimoto, Shin-ichi; Terada, Kenjiro; Sato, Masami; Hashida, Toshiyuki; Sato, Kazuhisa; Iguchi, Fumitada; Yugami, Hiroo; et al.
Abstract : Long-term reliability and durability are of great importance for the commercialization of SOFCs. Mechanical behaviors of ceramics components, including cell fracture, are necessary to be understood in order to ensure stability of SOFCs. For the multiscale simulation of the thermo-chemo-mechanical behavior, various related materials properties are indispensable. This paper reports the evaluation procedure of material properties for comprehensive analysis of chemically- and thermally induced mechanical behavior of SOFCs.